2017
DOI: 10.1080/19371918.2017.1289872
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Rural and Urban Cervical and Breast Cancer Screening Rates in a Privately Insured Population

Abstract: Low preventive screening varies by region and contributes to poor outcomes for breast and cervical cancer. Previous comparative urban and rural research on preventive screening has focused on government programs. This study quantified and compared rural and urban preventive cancer screening rates for women who were privately insured. National Quality Forum measures were used to calculate rates for women within rural and urban parts of the same Hospital Referral Region (HRR) using claims data. Mammography scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…34 Another recent claims-based study of breast and cervical cancer screening, from the commercially insured population, found rural residence as an important predictor of screening status. 35 These findings suggest that despite addressing the economic disparities in access to care through expanded insurance coverage and the elimination of out-of-pocket costs for these preventive cancer screenings, a complex matrix of logistic and sociocultural barriers to care persist. Increasing contact with primary care remains the critical first step to improving coordination of care.…”
Section: Discussionmentioning
confidence: 99%
“…34 Another recent claims-based study of breast and cervical cancer screening, from the commercially insured population, found rural residence as an important predictor of screening status. 35 These findings suggest that despite addressing the economic disparities in access to care through expanded insurance coverage and the elimination of out-of-pocket costs for these preventive cancer screenings, a complex matrix of logistic and sociocultural barriers to care persist. Increasing contact with primary care remains the critical first step to improving coordination of care.…”
Section: Discussionmentioning
confidence: 99%
“…Given the delay between exposure and outcome, a more immediate strategy would be to increase cancer screening (eg, cervical) availability and utilization among rural residents. Studies have reported that rural residents are less likely to receive cancer screening than their urban peers . Further, rural residents are more likely to state cost as a factor in not receiving screening, have less access to specialty cancer care, not receive physician recommendations for screening, and experience higher rates of screening‐preventable cancers and higher cancer mortality .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with individuals working in agriculture, it was 7% (9). In a study conducted in the United States, the rate of individuals undergoing FOBT in rural areas was 22% (30). According to the results of our study, there is a substantial need of raising awareness regarding colorectal cancer screening in Turkey.…”
Section: Discussionmentioning
confidence: 59%